A Low - Cost Effective Therapy Of Pastular Dermatitis Atrophicans(PDA) - Ghosh Srabani; Lahiri Swapan Kr; Dutta Ajit Kr (Wolters Kluwer Medknow Publications, 1995)
The clinical entity PDA mainly affects lower socio- economic group in tropical countries. Its cure/control poses a challenge to dermatologists. To evaluate a low â€" cost drug therapy, dapsone was tried among patients of chronic folliculitis of legs along with tropical providone â€" iodine application. Forty- two patients who came for regular follow â€" up revealed satisfactory result with marked improvement in about 70% cases with minimal side- effects. The antibacterial and immunomodulatory action of dapsone may be beneficial in these cases. The possible role of androgen triggering effect remains an open question in its pathogenesis and chronicity.